Percepção de pacientes sobre a internação em um hospital universitário: implicações para o ensino médico - Cortopassi, Andrea Christina [UNESP]; Lima, Maria Cristina Pereira [UNESP]; Gonçalves, Irio José [UNESP] (Associação Brasileira de Educação Médica, 2006)
Objective: Evaluate how inpatients perceive the relationships established with professionals and students during their stay in the Botucatu Medical School Hospital (FMB-Unesp). Methodology: Observational study, in which information was collected through interviews for obtaining data about the hospitalization and using the technique of a focus group with patients from one of the hospital wards. Results: The hospitalization was evaluated as good or excellent by the greater part of patients both in the interviews and in the focal group. The few complaints that arose referred mainly to the doctors' rounds. Conclusions: Although the evaluations were positive, the patients were ambivalent in relation to the doctors' rounds. Guidelines providing orientation for how these rounds should be performed are necessary so that they can preserve their didactic role without affecting the patient. Institutional strategies for continuous quantitative and qualitative evaluation should be developed, especially in university services.

Objetivo: Avaliar a percepção dos pacientes quanto à relação estabelecida com profissionais e alunos durante internação no Hospital das Clínicas da Faculdade de Medicina de Botucatu (FMB-Unesp). Metodologia: Trata-se de um estudo observacional, no qual as informações foram colhidas por meio de entrevistas para obter dados sobre as internações, tendo sido realizado também grupo focal com pacientes de uma das enfermarias. Resultados: A internação foi avaliada como boa e ótima pela maior parte dos pacientes, tanto nas respostas às entrevistas quanto no grupo focal. As poucas queixas que surgiram foram dirigidas principalmente à visita médica. Conclusões: Embora as avaliações tenham sido positivas, os pacientes se mostraram ambivalentes em relação à visita médica. Diretrizes que norteiem sua realização são necessárias para que a mesma preserve seu papel didático sem prejuízo para o paciente. Estratégias institucionais de avaliação contínua devem ser desenvolvidas, especialmente em serviços universitários, aliando metodologias quantitativas e qualitativas.
Patients' perception of hospitalization in a university hospital: implications for medical teaching
Keywords: Education,Medical; Physician-Patient Relations; Psychology, Medical; Educação Médica; Relações Médico-Paciente; Psicologia Médica